2023
DOI: 10.3390/nursrep13030105
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice Competency of Registered Nurses in the Greek National Health Service

Stefania Schetaki,
Evridiki Patelarou,
Konstantinos Giakoumidakis
et al.

Abstract: Nurses’ competency toward evidence-based practice (EBP) has been extensively investigated by several studies worldwide. However, factors affecting the competence of Greek nurses working in the NHS have not been fully investigated in terms of EBP. Thus, this study aimed to explore the impact of the individual qualifications of nurses on their competence toward EBP. Data from 473 registered nurses working in 10 hospitals in the Greek National Health Service (NHS) were collected between October and December 2020 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Effective communication (C75-C80) and emergency response and crisis management (C81-C87) competencies in virtual healthcare are important aspects of ensuring collaborative teamwork and fostering safe patient care [33]. Similarly, practitioners with competencies in research development and evidence-based practice guarantee high-quality healthcare outcomes [13]. In addition, "Digital marketing will play a role in promoting telehealth services and educating patients and society about its benefits" [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective communication (C75-C80) and emergency response and crisis management (C81-C87) competencies in virtual healthcare are important aspects of ensuring collaborative teamwork and fostering safe patient care [33]. Similarly, practitioners with competencies in research development and evidence-based practice guarantee high-quality healthcare outcomes [13]. In addition, "Digital marketing will play a role in promoting telehealth services and educating patients and society about its benefits" [8].…”
Section: Discussionmentioning
confidence: 99%
“…SEHA Virtual Hospital (SVH) is the first virtual hospital in the Middle East and North Africa and the first hospital worldwide to obtain Canadian accreditation. It offers more than 29 specialties and 73 subspecialties [13]. It is connected to a network of over 170 hospitals across all regions in Saudi Arabia.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge, Greek nurses' knowledge, attitudes and implementation of EBP [21,22], especially in community nurses [23], is understudied. In particular, it was found that the majority of the participants did not have an in-depth knowledge of EBP and did not implement it in clinical practice [21].…”
Section: Introductionmentioning
confidence: 99%
“…In another study [24], in a sample of midwives and midwifery students, 43.5% of the participants stated that they knew the term EBP, with the first source of information being colleagues (52.2%) and the second searching the internet in general (48.8%), but not in EBP databases. Schesaki et al [22], in a recent study, indicated that factors such as holding a master's degree, having experience in writing academic papers, working in a university clinic and possessing computer skills had a positive influence on hospital nurses' attitudes, knowledge, skills and practices. In the only study involving a sample of community nurses, it was revealed that approximately half of these nurses were acquainted with EBP and held favorable attitudes toward it.…”
Section: Introductionmentioning
confidence: 99%